The hemophilia quality of life scale: a systematic review - Wang, Xin; Li, Zhixiao; Li, Lele (Frontiers in Public Health, 2024)
Purpose Quality of life refers to the degree of well-being a person feels. The development of a hemophilia-targeting quality of life scale is important for hemophiliacs and their treating physicians. Methods Textual analysis. First, a review of studies on quality of life, hemophilia and related quality of life scales was conducted; Subsequently, two rounds of systematic searches of the Springer database were conducted to filter the literature on universal quality of life scale studies and hemophilia-targeting quality of life scale studies by title and abstract, and then textual analysis was performed.The former included 77456 articles, 26117 chapters and 7086 related bibliographies, while the latter initially retrieved 211 entries articles, 118 chapters and 43 related bibliographies. Through filtering, the former contains 22 documents, yielding 1431 valid word stems, and the latter contains 9 documents, yielding 1541 valid word stems. Conclusion While universal quality of life scales mostly fit into the broad framework of WHOQoL-BREF, the development of hemophilia-targeting quality of life scales inclines towards pains that patients suffer and technology advances in pharmaceutical. The current hemophilia QOL scales are mainly based on the HR-QoL, others mainly based on the HR-QoL as the master version. At the same time, the popularization of existing hemophilia quality of life scales in developing countries like China is not high, and the development of hemophilia quality of life scales is insufficient. Keywords quality of life • hemophilia • quality of life scale